INFLUENCE OF INSTITUTIONAL OWNERSHIP AND UTILIZATION OF TAX HAVEN TO THIN CAPITALIZATION - Nofryanti Nofryanti; Tuty Nurjanah (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
This study aims to find out the influence of instituonal ownewrship and utilization of tax haven and with Thin capitalization. Sample in this study is 21 with criterias: manufacturing companies in indonesia stoct exchange for the periode 212-2016. Analysis were conducted byusing multiple regression analysis. The result shows that instituonal ownweship has negative influence on thin capitalization, while the utilization of tax haven has no significant influence on thin capitalization.